Rancang Bangun Media Informasi Wisata Alam Di Kabupaten Murung Raya Berbasis Website - Nurhuda, Thomas; Putra, Putu Bagus Adidyana Anugrah (Journal of Information Technology and Computer Science, 2022)
The rapid development of technology encourages people to use technology to develop. Technological advances have had a huge impact on the world of information technology. Therefore the author took the initiative to create a website for Nature Tourism Information Media in Murung Raya Regency which is expected to provide information about natural tourism in Murung Raya Regency.The methodology used in making the Nature Tourism website in Murung Raya Regency is the waterfall methodology, with the stages, namely the Requirements definition stage described using a flowchart. Requirements analysis and definition is illustrated through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram) and database. Implementation and unit testing with the programming languages used, namely HTML, PHP, CSS, Bootstrap, Javascript and MySQL. Integration and system testing uses the blackbox testing method.